Innate immune biology in age-related macular degeneration - Ascunce, Karina; Dhodapkar, Rahul M.; Huang, Deven; Hafler, Brian P. (Frontiers in Cell and Developmental Biology, 2023)
1 Age-related macular degeneration (AMD) is a neurodegenerative disease and a leading cause of irreversible vision loss in the developed world. While not classically described as an inflammatory disease, a growing body of evidence has implicated several components of the innate immune system in the pathophysiology of AMD. In particular, complement activation, microglial involvement, and blood-retinal-barrier disruption have been shown to play key roles in disease progression, and subsequent vision loss. In AMD changes occur within the peripheral immune system including changes to the blood-retina barrier structure, and microglial cell, monocyte-derived macrophage, and complement activation. This review discusses the role of the innate immune system in AMD as well as recent developments in single-cell transcriptomics that help advance the understanding and treatment of AMD. We also explore the several potential therapeutic targets for AMD in the context of innate immune activation.